Reproduction after the loss of a child: a population-based matched cohort study. Issue 8 (10th July 2018) - Plana-Ripoll, O; Basso, O; László, K D; Olsen, J; Parner, E; Cnattingius, S; Obel, C; Li, J
Abstract: STUDY QUESTION: Is the death of a child associated with higher subsequent fertility? SUMMARY ANSWER: Women who had lost a child had higher fertility both shortly after the loss and throughout the entire follow-up, independent of the child's age at the time of death. WHAT IS KNOWN ALREADY: Women who lose a child in the perinatal period often have another child shortly after. However, to our knowledge no previous study has investigated if the death of an older child affects reproductive behavior. STUDY DESIGN, SIZE, DURATION: The source population for this matched cohort study consisted of all women who gave birth in Denmark from 1978 to 2004 and in Sweden from 1973 to 2002 ( N = 1 979 958). Women were followed through to the end of 2008 in Denmark and the end of 2006 in Sweden. PARTICIPANTS/MATERIALS, SETTING, METHODS: Women who had lost a child before the age of 45 years during the study period (exposed group; n = 36 511) were matched with up to five women who were from the same country and of similar age and family characteristics and had not lost a child at the time of matching (unexposed group; n = 182 522). MAIN RESULTS AND THE ROLE OF CHANCE: During follow-up, 74% of exposed and 46% of unexposed women had another birth (live- or stillbirth) after a gestation of 28 weeks or more. Compared with unexposed women, exposed women had a shorter interpregnancy interval and, consequently, a higher rate of conception leading to a birth (HR = 5.5 [95% CI: 5.4–5.6]). Rates for exposed women were higher from the first month following the child's death, but the largest difference was between 2 and 3 months after the event. This pattern was independent of the age of the deceased child. Exposed women had more subsequent children than unexposed, leading to a comparable number of living children at the end of follow-up. LIMITATIONS, REASONS FOR CAUTION: The use of population-based registers allows for the inclusion of virtually all eligible women and nearly complete follow-up; the potential for selection bias is thus negligible. However, only pregnancies that led to a live birth or a stillbirth could be identified, thus fetal losses occurring before week 28 of gestation were missing. WIDER IMPLICATIONS OF THE FINDINGS: Our findings corroborate the previous evidence suggesting that women try to conceive again shortly after a perinatal death, and many succeed. In addition, this is the first study to investigate the reproductive trajectory after losing an older child. The current study indicates that most women who lose a child between the ages of 6 months and 5 years conceive shortly after the loss, and they have a comparable number of living children at the end of the follow-up compared to those who do not lose a child. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by Grant ERC-2010-StG-260242 from the European Research Council, 176673 and 186200 from the Nordic Cancer Union, DFF-6110-00019 from the Danish Council for Independent Research, 904414 and 15199 from TrygFonden, Karen Elise Jensens Fond (2016), and the Program for Clinical Research Infrastructure (PROCRIN) established by the Lundbeck Foundation and the Novo Nordisk Foundation. The authors do not declare any conflicts of interests. TRIAL REGISTRATION NUMBER: N/A.